Economic Policy and Institutions of the Regional Development - Kayukov, Vladimir Viktorovich; Lazhentsev, Vitaly Nikolayevich; Shikhverdiev, Arif Pirvelievich (Economy of Regions, 2019)
The article considers the problems of improving the economic system and shaping the relevant rules and norms of economic activities in the context of the institutionalism’s growing importance. We analyse the possibility to use the «agreement theory» and «philosophy of co-operation» for explaining the essence of economic policy as a whole, regional policy of the state and economic policy of the regions (constituent entities of the Russian Federation). In the institutional approach, the key role belongs to the coordination of interests that is both an objective law of public development and the way to overcome critical situations. We characterise subsystems of the «agreement theory», including an exchange of commodities, production and technologies, traditional economic activities, ecology, civil society, public opinion, creative activities. The obtained «matrix of understanding» might be used as a «roadmap» of the economic policy at all levels (state, region, company) taking into account an obligatory adjustment for the specificity of the national economy and its spatial arrangement. We have underlined that the general theoretical concepts of economic policy can not be applied to the regional policy. The whole (national economy) cannot be reduced to the sum of the parts (regional economies), thus, many macroeconomic processes and events are not traced in its individual components. In the regional development, the institution of economic federalism plays the key role. We have defined the spheres of the regions’ economic activities, where regional efforts can lead to the positive result. Such spheres include property relations, rational nature management, price policy, fiscal and credit-and-monetary spheres, regulatory actions of the relations between the state and regional authorities, and interregional integration.